Artikel PELATIHAN PEMBUATAN FILM PRAKTIS BERBASIS KEBUDAYAAN TEMPATAN BAGI KOMUNITAS EKSPLORASI RINTIS SENI (KERIS) PASIR PENGARAIAN - ulim@ muslim; Rita Arianti; Hermawan; Nuratika; Tia Fijri Astuti (JURNAL MASYARAKAT NEGERI ROKANIA, 2026)
ABSTRACT The massive development of communication technology has had a dual impact: it serves as a means of information and also poses a potential threat to foreign cultural hegemony, eroding local moral and aesthetic values. One strategic effort to strengthen cultural bulwarks is to actively utilize communication technology through the production of content based on local wisdom. This community service activity aims to equip members of the Pasir Pangaraian Art Pioneer Exploration Community (KERIS) with practical skills in short filmmaking as a medium for promoting local culture. The method used was a three-day intensive training that included an explanation of film theory, crew management, scriptwriting, cinematography practice, and the short film production process. The results of this community service activity were an increased understanding of camera features and production management, as well as the successful production of a practical short film entitled "Tuah Kampung." Evaluations demonstrated a positive response and high enthusiasm from partners, with recommendations for continued participation in public film screenings and improvements to supporting equipment.